STAT3 silencing by an aptamer-based strategy hampers the crosstalk between NSCLC cells and cancer-associated fibroblasts - Maria L. Ibba; Giuseppe Ciccone; Deborah Rotoli; Gabriele Coppola; Alfonso Fiorelli; Silvia Catuogno; Carla L. Esposito (Elsevier, 2023)
The identification of new effective therapeutic options for non-small-cell lung cancer (NSCLC) represents a crucial challenge in oncology. Recent studies indicate that cancer-associated fibroblasts (CAFs) participate in tumor progression by establishing a favorable microenvironment that promotes cancer progression. Therefore, the development of strategies inhibiting the interplay between CAFs and cancer cells is considered a winning approach for the development of effective anti-cancer drugs. Among other factors, the signal transducer and activator of transcription-3 (STAT3) has been reported as a key mediator of CAF oncogenic actions, representing a promising therapeutic target. Here, we applied an aptamer-based conjugate (named Gint4.T-STAT3), containing a STAT3 siRNA linked to an aptamer binding and inhibiting the platelet-derived growth factor receptor (PDGFR)β, to obtain STAT3-specific silencing and interfere with CAF pro-tumorigenic functions. We demonstrated that this molecule effectively delivers the STAT3 siRNA in NSCLC cells, and blocks CAF-induced cancer cell growth and migration and reduced spheroid dimension. In addition, we found that Gint4.T-STAT3 alters CAF phenotype, thus functioning as a double-acting molecule able to inhibit the entire tumor bulk. Our data provide a proof of principle for the targeting of CAF pro-tumor functions through an aptamer-based drug, and can open innovative horizons in NSCLC therapy.